Challenges and Learning from Remote Teaching of Usability and UX: An Experience Report - Marques, Leonardo; Matsubara, Patrícia Gomes Fernandes; de Souza, José Cezar; Junior, Genildo Gomes da Silva; Gadelha, Bruno Freitas; Conte, Tayana Uchoa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2020: Anais do XIX Simpósio Brasileiro de Qualidade de Software, 2020)
Social isolation was a strategy adopted during the COVID-19 pandemic to slow down transmitting the disease-causing virus. Some higher education institutions have adopted Emergency Remote Education (ERE) to avoid the complete suspension of classes in this context. However, the ERE poses specific challenges for the teaching and learning process. In this work, we present an experience report in a course that addresses usability and UX concepts, essential aspects of software quality, in the ERE modality. We discuss the methodology adopted and the students’ perception of this experience. Our results show that, even in a remote context, students considered the execution of practical assignments on usability and UX assessments in innovative software systems as the element that most contributed to learning. However, they also pointed out the challenges faced in carrying them out, such as recruiting people to participate in the assessment due to social isolation. Also, students reported their experiences in the practical use of UX techniques to assess the software's quality from the user's perspective, indicating both the perceived positive and negative aspects. These findings can help teachers make decisions about which approaches are more suitable for remote teaching.